UPLC-MS/MS method for simultaneously determining nucleosides and methyl-nucleosides in liver mRNA of Epimedin C-induced liver injury mouse model - Zhizhen Song; Zeyun Li; Xueqian Wen; Ruijuan Liu; Xin Tian (BMC, 2021)
Abstract Background Epimedin C, one of the main active ingredients of Epimedium, has been reported to have potential hepatotoxicity. However, the mechanism of Epimedin C-induced liver injury has not been studied. mRNA methylation, mainly including N6-methyladenosine and N5-methylcytidine, is implicated in the regulation of many biological processes and diseases. The study of quantifying mRNA methylation alterations in Epimedin C-induced liver injury mice may contribute to clarify the mechanism of its hepatotoxicity. Therefore, an analysis method needs to be established to determine nucleoside and methyl-nucleoside levels in liver mRNA. Methods An ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was developed and validated to simultaneously determine six nucleosides (adenosine, uridine, cytidine, guanosine, N6-methyladenosine and N5-methylcytidine) in liver mRNA. Besides, the Epimedin C-induced liver injury mouse model was studied by intragastrical administration Epimedin C at a daily dose of 10 or 40 mg/kg for 4 weeks. The nucleoside samples of the mice liver mRNA were prepared and separated on an UPLC column using 0.1% formic acid water and methanol after enzymatic digestion. Then the sample was detected by a Qtrap 6500 mass spectrometer. Results In this method, calibration curves of the six nucleosides showed good linearity over their concentration ranges. The linear ranges were 40-20,000 pg/mL for adenosine, cytidine, N6-methyladenosine and N5-methylcytidine, 0.2-100 ng/mL for guanosine, and 2-1000 ng/mL for uridine. Epimedin C-induced liver injury mouse model was successfully established,which could be proved by the elevation of serum aminotransferase levels, and the increased inflammatory cell infiltration as well as vacuolar degeneration in liver. The N6-methyladenosine and N5-methylcytidine levels, and the ratios of N6-methyladenosine to adenosine and N5-methylcytidine to cytidine of the mice liver mRNA were all significantly increased after Epimedin C treatment. Conclusion The established method was successfully applied to the determination of six nucleosides levels in liver mRNA of the Epimedin C-induced liver injury mice model and the control group. The results indicated that mRNA methylation might be associated with Epimedin C-induced liver injury. This study will facilitate the mechanism research on the hepatotoxicity of Epimedin C.